Effect of post weld heat treatment on the microstructure and properties of Laser-TIG hybrid welded joints for CLAM steel - Li, Xianfen (2020)
In this paper, the Laser-TIG hybrid weld joints of China low activation martensite (CLAM) steel were produced, and then experienced different post weld heat treatment (PWHT) to achieve a good combination of strength and toughness. The microstructure and mechanical properties of the joints were investigated. Meanwhile, the performance of weld joints before and after PWHT subjected to transient heat loads were studied by using a laser beam thermal load test to simulate the transient events in the future fusion reactors. The results indicate that the microstructure of the as-deposited weld metal (WM) was composed of coarse lath martensite and a small amount of hard delta-ferrite, leading to relatively high tensile strength, but low impact toughness (only 16.5% of parent metal). After PWHT, M23C6 type carbides were precipitated along lath martensite and prior austenite grain boundaries. With the prolonging of PWHT, the amount and size of precipitates were increased. After PWHT at 760 °C for 2 h, the precipitates were aggregated. The strength of the weld joints was slightly weakened but acceptable, while the toughness of the weld joints significantly increased, with evidence of many dimples in the ductile fracture surface. After transient heat loads with laser power densities up to 205.7 MW/m2, surface damage such as cracks, pits, re-solidified metal and oxidation were observed, the WM subjected to PWHT at 760 °C for 0.5 h appeared better performance of resistance to oxidation. Hence, PWHT at 760 °C for 0.5 h was suggested for the Laser-TIG hybrid weld joints of CLAM steel, which gave rise to sufficient strength, high toughness and excellent resistance to oxidation.